Potential Application of Lonicera japonica Extracts in Animal Production: From the Perspective of Intestinal Health - Tang, Xiaopeng; Liu, Xuguang; Zhong, Jinfeng; Fang, Rejun (Frontiers in Microbiology, 2021)
Lonicera japonica (L. japonica) extract is rich in active substances, such as phenolic acids, essential oils, flavones, saponins, and iridoids, which have a broad spectrum of antioxidant, anti-inflammatory, and anti-microbial effect. Previous studies have demonstrated that L. japonica has a good regulatory effect on animal intestinal health, which can be used as a potential antibiotic substitute product. However, previous studies about intestinal health regulation mainly focus on experimental animals or cells, like mice, rats, HMC-1 Cells, and RAW 264.7 cells. In this review, the intestinal health benefits including antioxidant, anti-inflammatory, and antimicrobial activity, and its potential application in animal production were summarized. Through this review, we can see that the effects and mechanism of L. japonica extract on intestinal health regulation of farm and aquatic animals are still rare and unclear. Further studies could focus on the regulatory mechanism of L. japonica extract on intestinal health especially the protective effects of L. japonica extract on oxidative injury, inflammation, and regulation of intestinal flora in farm animals and aquatic animals, thereby providing references for the rational utilization and application of L. japonica and its extracts in animal production.